Carvacrol instigates intrinsic and extrinsic apoptosis with abrogation of cell cycle progression in cervical cancer cells: Inhibition of Hedgehog/GLI signaling cascade - Ahmad, Afza; Tiwari, Rohit Kumar; Saeed, Mohd; Al-Amrah, Hadba; Han, Ihn; Choi, Eun-Ha; Yadav, Dharmendra K.; Ansari, Irfan Ahmad (Frontiers in Chemistry, 2023)
There is a strong rationale to therapeutically target the hedgehog (HH)/GLI signaling pathway in cervical cancer as active involvement of HH signaling is reported in cervical carcinogenesis and its association with recurrence and onset of chemoresistance. Our previous report have demonstrated that carvacrol (CAR) exhibited strong suppressive activity on Notch signaling pathway in prostate cancer cells, providing a foundation to further explore its antiproliferative activity in cervical carcinoma cells. Herein, the present study aimed to investigate the anticancer and apoptotic potential of CAR on C33A cervical cancer cells and further explore the underlying mechanisms. We found that CAR significantly suppressed the growth of C33A cells, induced cell cycle arrest, and enhanced cell apoptosis, accompanied by augmented level of ROS, dissipated mitochondrial membrane potential, activated caspase apoptotic cascade, and attenuated HH signaling cascade. CAR treatment increased expression of pro-apoptotic proteins (Bax, Bad, Fas-L, TRAIL, FADDR, cytochrome c) and decreased levels of the anti-apoptotic proteins (Bcl-2 & Bcl-xL) in C33A cells. CAR mediates the activation of caspase-8 & -9 (intrinsic pathway) and caspase-8 (extrinsic pathway) along with the PARP cleavage in cervical cancer cells. Thus, CAR induces apoptosis by both the intrinsic and extrinsic pathways. CAR efficiently inhibited the growth of cervical cancer cells via arresting cell cycle at G0/G1 transition and modulating G0/G1 transition related proteins (p21, p27, cyclin D1 and CDK4). Moreover, CAR inhibited the HH/GLI signaling pathway by down regulating the expression of SMO, PTCH and GLI1 proteins in cervical carcinoma cells. With evidence of above results, our data reveal the inhibitory effect of CAR on C33A (HPV-) cervical cancer and shed new light on the molecular mechanism of its therapeutic effect.